Parenting Styles as Predictors of Dimensions of Self-Efficacy in Students of Elementary Music School - Kostić, Senka M.; Minić, Jelena Lj.; Rovčanin, Elma E. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The basic problem of the research was contained in the question of whether the educational styles (authoritarian, authoritative and permissive) were statistically significant predictors of dimensions of self-efficacy (academic, social and emotional) in primary music school students. The sample was apposite and consists of 160 students of elementary music school, uniform by gender (80 boys and 80 girls). The PSDQ questionnaire (for measuring parenting styles) and the self-efficacy questionnaire for children were used in the study. Results showen that the students of elementary music school exhibited a high degree of self-efficacy on all three dimensions; as well as experiencing the parenting style of parents as like authoritative. Parenting styles proved to be good predictors of academic (r2 =0.25) and social (r2 = 0.22) self-efficacy; while it is not possible to predict the degree of emotional self-efficacy in students of elementary music school based on their knowledge of parenting styles.